Psychological implications of drawing a home for children who survived a terrorist massacre: Clinical study as part of the Psychological Counseling - Toutaoui, Karima (Journal of Human Sciences, 2023)
The psychological meanings of the drawing of the house of five children who survived the terrorist massacres refer to the effects of psychic trauma more than a year after the date of the terrorist massacre in the suburbs of the capital. The terrorist invasion of homes has generated a break-in of the children’s family, bodily and psychic envelopes, and a state of post-traumatic stress, which mobilizes either manic-depressive defenses, a strong emotional ambivalence or identification with the aggressor. It follows from this clinical analysis, the importance of the psychological function of the house, it is about a material and symbolic framework which supports the feeling of security of the self, and that any incident compromising this function risks to involve an imbalance in the psychic space of the child.